PENDIDIKAN KESEHATAN BERBASIS EMO DEMO (EMOTIONAL DEMONSTRATION) DALAM MENINGKATKAN PENGETAHUAN REMAJA TENTANG BAHAYA MEROKOK DI WILAYAH KOTA SURABAYA - Fajriyah, Novita; Rukmini, Rukmini; D.S, Rhesa Indah; Pratama, Joan Aurelia; Novita, Wahyu Dias; Amilia, Lina; Alfinazzahra, Fifitra Fillaili (Community Development in Health Journal, 2023)
Introduction & Aim: Smoking can be life-threatening and can be fatal. This phenomenon is widespread, especially among teenagers. Most smokers start smoking in their teens. Knowledge about the dangers of smoking in adolescents is still limited, where adolescents only know that smoking is not good for health, but do not have extensive knowledge about the dangers of smoking to their own health and the environment. Health education based on Emo Demo (Emotional Demonstration) is expected to increase youth's knowledge about the dangers of smoking. Method of Activity: Community service is carried out for youth in the Surabaya City Region, using lecture, demonstration, discussion and question and answer methods. The initial stage of registration and distribution of leaflets, filling out the Pre-Test quiz. The implementation phase uses lecture methods, discussions, followed by demonstrations and simulations. The final stage is evaluation, participants are asked questions by the presenter regarding the topics that have been explained and post test quizzes. Activity results: The level of knowledge of adolescents before being given health education on the dangers of smoking was mostly 43.75% insufficient, 25.00% sufficient, and 31.25% good. After being given Emo Demo-based Health Education there was an increase in adolescent knowledge about the dangers of smoking, 50.00% had good knowledge, 43.75% had enough, and 6.25 had less. Discussion: Changes in attitude due to increased knowledge show that Health Education based on Emo Demo (Emotional Demonstration) about the dangers of smoking is effective in conveying health information.